(untitled) (Sciences & Technology. A, exactes sciences, 2004)
This study concerns the numerical simulation of the three dimensional forced and mixed convection heat transfer in a uniformly horizontal heated pipe. The complete Navier-Stokes equations are numerically solved with a finite volume method.. The obtained results show that the mixed convection flow is quite three-dimensional. As the Grashof number is increased, a secondary flow develops in the form of a two counter-rotating vortices. The vortices lead to a better mixing of the flow and thus enhance the convective heat transfer: the local axial Nu decreases along an entrance region and then increases downstream instead of leveling off as in the case of forced convection. The increase is more important for higher Richardson numbers